Pendidikan Islam dan Moderasi Beragama Berbasis Pesantren: Studi atas Kurikulum dan Metode Pembelajaran - Rofiqi, Rofiqi (Universitas Nurul Jadid, 2025)
Islamic boarding schools (pesantren) play a strategic role in shaping a moderate and inclusive understanding of Islam, especially in multicultural societies like Bali. This study aims to analyze how Pesantren Nurul Jadid Bali implements Islamic education based on religious moderation through its curriculum and teaching methods. Using a qualitative approach and case study methodology, this research examines the curriculum structure, teaching strategies, and their impact on students' (santri) understanding and attitudes toward social life. The findings reveal that the pesantren's curriculum integrates classical Islamic studies, character education based on moderation, and interfaith understanding. The teaching methods employed include talaqqi (direct learning from teachers), interactive discussions, as well as social and experiential learning with the local community. Additionally, students are equipped with practical skills and foreign language proficiency to enhance their capabilities in the global era. Moreover, integrating local wisdom values into the curriculum has proven effective in fostering tolerance and social harmony. The interaction between students and Hindu and non-Muslim communities through social activities and interfaith dialogues strengthens their understanding of religious moderation. Thus, pesantren not only serve as centers for Islamic education but also as agents of social change, promoting harmony within religious diversity.